2001
DOI: 10.1538/expanim.50.83
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation and Transport of Mouse Spermatozoa at -79.DEG.C..

Abstract: Abstract:In the present study, 2 experiments were carried out. In experiment 1, mouse spermatozoa were frozen and stored in an ultra-low temperature freezer maintained at -79°C, from 1 week to 8 months. In vitro fertilization rates of the frozen-thawed sperm after 1 week and 4 months of storage were high at 71 and 71%, respectively. These values did not differ significantly from the value (73%) of the control stored at -196°C. In contrast, the 8-month storage rate was significantly lower at 51%. In experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…With regard to mouse spermatozoa, Okamoto et al reported [38] that outbred or hybrid stocks' spermatozoa could be stored at −79°C up to 4 months before losing fertility or could be successfully transported nationally in dry ice.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to mouse spermatozoa, Okamoto et al reported [38] that outbred or hybrid stocks' spermatozoa could be stored at −79°C up to 4 months before losing fertility or could be successfully transported nationally in dry ice.…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al (10) have found that, during tissue freezing and thawing cycles, both the formation of ice crystals and the osmotic effect contribute to RNA degradation. In another study, it was found that RNA and DNA were stable only up to five hours after the tissue was excised when the tissue was maintained at room temperature (5).…”
Section: Discussionmentioning
confidence: 99%
“…These parcels are fully disposable, eliminating the need for the receiving facility to return a dry shipper. It is also a safer laboratory practice, as there is a reduced need to handle LN 2 (Okamoto et al, 2001).…”
Section: Transporting Frozen Sperm On Dry Icementioning
confidence: 99%